Diversity and socio-cultural importance of wild food herbs and cyanobacteria in the Lake Chad Basin (Niger) - Rabiou, Habou; Maazou, Rahila; Mahamane, Mansour; Issaharou-Matchi, Issiaka; Mahamane, Ali; Lykke, Anne Mette (Ethnobotany Research and Applications, 2023)
Background: Wild herbaceous food species are declining throughout the Sahel region, particularly in the south-eastern corner of Niger, where settlements of thousands of refugees from Boko Haram, in addition to the native people, generate high pressure on the herbaceous food species. The objective of this study is to assess the use of wild herbaceous food plants in two departments in the Lake Chad Basin. Methods: Ethnobotanical surveys were conducted with 270 informants asked about their use of these plants for food including parts consumed, food categories, economic value and impact of exploitation. Results: A total of 32 wild herbaceous species, mainly from the family Poaceae (21.8%) and dominated by the life form Therophytes (43.7%), were cited. According to the respondents, the most consumed parts were the leaves with 51.2% and 41.3% of the citations in Mainé Soroa and N’Guigmi, respectively. Seeds were cited by 26.8% of the informants in Mainé Soroa and 30.7% in N’Guigmi. Fruits were cited by 19.2% and 26.2% in Mainé Soroa and N’Guigmi, respectively. The least consumed parts were roots and flowers. The species preference depends on the ethnic group. Refugees who had recently settled in the area stood out with a consumption of other species than the native people. Informants from Mainé Soroa and N’Guigmi stated that 52% and 44% of the species, respectively, were becoming increasingly scarce. The main causes of the degradation of these resources were agriculture, drought and overexploitation. Conclusions: In general wild herbaceous food resources play a very important role in the Lake Chad Basin, where people live insecure lives. Keywords: Herbaceous food plants, indigenous plants, local knowledge, Lack Chad Basin, Niger.